Phytate destruction consequences for precision animal nutrition - Walk, Carrie L.; Kühn, Ingolf; Stein, Hans H.; Kidd, Michael T.; Rodehutscord, Markus 1962- (Wageningen Academic Publishers, 2016)
Incorporating research chapters from academic authors around the world, this book focuses on the most recent scientific advances in understanding phytate; both IP6 and its esters. It examines phytate degradation patterns in the gastrointestinal tract, and investigates the relevance of gut microbiome and endogenous phosphatases on phytate breakdown, as well as regulation and functions of inositol diphosphates IP3, IP4, and IP7, IP8. It also identifies recommendations for formulating for minerals and amino acids in the presence of phytate, including the effects of phytase on protein bioavailability, and the impact of digestible Ca and P in both swine and poultry. This leading science and research is coupled with real-world pragmatism, including a focus on what industry stakeholders are currently doing to counter dietary phytate, and an overview of the role of nutrition in respect of bone health, meat quality, welfare, and antibiotic free production. As such, the content is relevant for scientists, nutritionists and producers alike
Includes bibliographical references
Keywords: TECHNOLOGY & ENGINEERING / Agriculture / Animal Husbandry / bisacsh; Animal nutrition / fast / (OCoLC)fst00809306; Animal nutrition; Phytate; Tierernährung; Verdauung